Generalized Tetranacci hybrid numbers - Soykan, Yüksel; Taşdemir, Erkan (Annales Mathematicae Silesianae, 2020)
In this paper, we introduce the generalized Tetranacci hybrid numbers and, as special cases, Tetranacci and Tetranacci-Lucas hybrid numbers. Moreover, we present Binet’s formulas, generating functions, and the summation formulas for those hybrid numbers.